2019
DOI: 10.1016/j.ijrobp.2018.09.041
|View full text |Cite
|
Sign up to set email alerts
|

DVH-Based Inverse Planning Using Monte Carlo Dosimetry for LDR Prostate Brachytherapy

Abstract: We proposed an inverse planning method based on dose-volume histogram optimization and Monte Carlo dosimetry. We compared plans calculated using our proposed method with clinical plans calculated using the TG-43 dosimetry formalism. We demonstrated that our method can provide plans with higher prostate dose homogeneity (up to 6.1%) and lower urethral dose (up to 4.0%) compared with the clinical plans. The computational time (37.5 AE 3.2 s) complies with intraoperative time restrictions.Purpose: Inverse plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Inspired by the work of [15], we performed an inverse planning based on dose-volume-histograms (DVHs) by using the Fast Simulated Annealing (FSA) algorithm [2]. The cost function to minimize, given by the equation 1, includes the different DVH dosimetric criteria given by the AAPM TG-137 recommendations [1]:…”
Section: Dvh-based Fsa For Inverse Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the work of [15], we performed an inverse planning based on dose-volume-histograms (DVHs) by using the Fast Simulated Annealing (FSA) algorithm [2]. The cost function to minimize, given by the equation 1, includes the different DVH dosimetric criteria given by the AAPM TG-137 recommendations [1]:…”
Section: Dvh-based Fsa For Inverse Planningmentioning
confidence: 99%
“…Even though, the inverse planning algorithms usually perform a thousand of iterations before obtaining a satisfactory solution, leading to a very long-time calculation to get the final optimized plan. A DVH-based optimization algorithm using MCS dosimetry for LDR prostate brachytherapy has previously proposed [15]. In this work, MCS is used to compute dose kernels for each single seed position, followed by the use of FSA.…”
Section: Introductionmentioning
confidence: 99%
“…After the completion of a conventional trial-and-error inverse planning procedure, the dose interval is identified to locate the voxels that receive the dose in the selected range. Mountris et al proposed an inverse planning approach that can improve planning quality by combining DVH without compromising the overall execution times [22]. However, most DVH-based optimization algorithms are mostly used in external radiotherapy, and only a small number of specialists consider the evaluation of DVH with the automatic optimization of seeds distribution.…”
Section: Purposementioning
confidence: 99%
“…In this paper we propose a novel method for automatic seeds localization in 3D US images. Connected to a fast replanning, 3 this allows to envision a fully automatic adaptive brachytherapy, that is an intraoperative update of the seeds placement planning, based on the localization and actual dosimetry map of the previously implanted seeds.…”
Section: Introductionmentioning
confidence: 99%
“…showed on patient date that orientations errors may have in impact on the dose delivered to organs at risks. Moreover adaptive brachytherapy involves more complex dose models 3 requiring a full localization of the seed. Finally, published methods differ in their level of evaluation.…”
Section: Introductionmentioning
confidence: 99%